Peran Pejabat Pengelola Informasi dan Dokumentasi Desa (PPID) dalam Masyarakat Berbasis Digital di Desa Sepit Kecamatan Keruak - Muhamad Zul’fahmi; Sukron Hadi; Samsul Hadi (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
Information is needed principal everyone shares development personal and environmental social as well as is part important for resilience national. The right to acquire information is right basic people and openness to information to the public is one of the characteristics a democratic country must uphold tall popular sovereignty to realize good state administration. Research purposes This is to know the Role of Officials Manager Village Information and Documentation in Services and Provisions Public Information in Sepit and Untuk Villages know the obstacles faced by PPID in service and provision information public in Sepit Village. Type of research used in study This is descriptive qualitative that is illustrative research something circumstances objects or incidents certain based on apparent facts or as it should be accompanied by effort taking conclusion general based on factor historical. Data collection techniques from the study This includes observation, interviews, and documentation. Informant research on the thesis This is Chairman of PPID in Sepit Village, Parties the Sepit Village PPID manager, and the Sepit Village community. Based on the results of research in the field Role of Officials Manager Village Information and Documentation (PPID) in digital-based communities in Sepit Village is quite optimal and sufficient by what is stated in number 14 of 2008 concerning openness information public and regulations Government Republic of Indonesia Number 61 of 2010 Concerning Openness Public Information. Then the barrier is lots of society that doesn't know related official manager information and documentation (PPID). Second, lack of understanding public public-related channel application information, and Keriga lacks a means of machine photocopy.